Pengurutan dan Rendam Kaki pada Air Suam Campur Parutan Kencur untuk Mengurangi Pembengkakan - Mayang Wulan; Utary Dwi Listiarini; Riska Dwi Permata (Prodi D III Kebidanan Fakultas Ilmu Kesehatan Universitas Ibrahimy, 2023)
In pregnant women aged 28-38 weeks, it is known that 80% experience swelling of the legs. This swelling is due to the accumulation of excessive fluid which is influenced by the hormone estrogen during pregnancy. Foot sequencing can minimize swelling and the brain will produce something so that the body calms down. Soaking the feet in warm water mixed with grated kencur is useful as a compress for swelling because it contains essential oils. This study aims to analyze the effectiveness of sequencing and soaking foot in warm water mixed with grated kencur to reduce leg swelling in pregnant women. The research method used a quasi-experimental without using a control group. The research location at BPM Hj. Ramayati Pohan Aceh Singkil District in April-February 2022. The sample used a purposive sample technique. The number of samples was 20 pregnant women who experienced leg swelling at 28-38 weeks of gestation. The Wilcoxon test was used in the bivariate test of this study. The results showed that there is an effect on the effectiveness of sequencing and soaking foot in warm water mixed with grated kencur in reducing leg swelling in pregnant women.